INTEGRAL FRAKSIONAL DARI FUNGSI HIPERBOLIK - Syifaul Janan (MATHunesa: Jurnal Ilmiah Matematika, 2025)
This study presented a fractional integral representation of hyperbolic sine and hyperbolic cosine function. The method used in this study involved the representation of the function in the form of a Maclaurin series, followed by the analysis of its fractional integral, and the determination of convergence interval. Furthermore, the computed results were visualized through simulations using MATLAB software. The results showed that when the fractional order alpha approaches 0, the graph obtained is getting closer to the initial function. Conversely, when alpha approaches 1, the graph is getting closer to the integral of the initial function. Keywords: Maclaurin series, hyperbolic function, fractional integral, Matlab